Novel alkaline copper CMP polishing solution and preparation method thereof

Through the new alkaline copper CMP polishing liquid, combined with components such as potassium hydroxide and glycine, the harm of acid polishing liquid to equipment and personnel is solved. The use of multi-wall carbon nanotubes and other components has been adopted to achieve efficient copper surface flattening and removal Rate, meet the high-quality needs of industrial production.

CN119243160APending Publication Date: 2025-01-03HEBEI UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411218205.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing copper CMP polishing liquids are mostly acidic, which harms the health of equipment and personnel. The inhibitor is highly toxic, difficult to dissolve in water, has low inhibition efficiency, and is difficult to achieve high removal rate and low surface roughness at the same time.

Method used

Using a new alkaline copper CMP polishing liquid, containing SiO2 abrasives, potassium hydroxide solution pH regulator, glycine complexing agent, dodecylbenzene sulfonic acid and 2-aminobenzimidazole composite inhibitor, multi-wall carbon nanotube lubricating The pH value of the agent is adjusted to 8-8.5 and is prepared by sonication and dissolving with sufficient stirring.

Benefits of technology

It realizes a non-toxic and harmless polishing liquid, reduces corrosion and scratches on the copper surface, ensures high removal rate and excellent surface quality, and meets industrial production needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243160A_ABST
    Figure CN119243160A_ABST
Patent Text Reader

Abstract

The invention discloses a novel alkaline copper CMP polishing solution and a preparation method thereof, and relates to the technical field of polishing solutions, the novel alkaline copper CMP polishing solution comprises a grinding material, a pH regulator, a complexing agent, an oxidizing agent, a composite inhibitor, a lubricant and deionized water, the grinding material is SiO2, the pH regulator is a potassium hydroxide solution, the composite inhibitor comprises dodecylbenzene sulfonic acid and 2-aminobenzimidazole, and the lubricant is a potassium hydroxide solution. The lubricant comprises a multi-walled carbon nanotube; according to the polishing solution, the removal rate can be effectively regulated and controlled, and the surface quality can be greatly improved; according to the polishing solution, the MWCNTs are added to serve as a lubricating agent, and scratches of abrasive materials to the copper surface are effectively reduced; the polishing solution is an alkaline polishing solution and is friendly to equipment and operators; inhibitors DBSA and 2-ABI used in the polishing solution are non-toxic and harmless and easy to dissolve in water, a layer of compact passive film can be attached to the copper surface, and corrosion of the polishing solution to the copper surface is effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polishing liquid, in particular to a novel alkaline copper CMP polishing liquid and a preparation method thereof. Background Art

[0002] Copper has low resistance, excellent thermal conductivity and anti-electromigration ability, and is widely used as the wiring layer material of integrated circuits. The surface morphology of the wiring layer has a serious impact on device performance. With the increase in the number of copper interconnect layers and the decrease in feature size in integrated circuits, the problem of uneven distribution between layers becomes more and more obvious, which brings huge challenges to the demand for nano-level lithography accuracy. Therefore, each layer needs to achieve nano-level flatness. At present, chemical mechanical polishing (CMP) is the most commonly used technology to achieve local and overall flattening of the wafer surface. As the most important consumable in the CMP process, the quality of the polishing liquid directly determines the surface quality of the polished wafer. However, the existing copper CMP polishing liquid still has the following problems: First, most commonly used polishing liquids are acidic, which will cause serious corrosion to the polishing equipment and endanger the health of the operators; Second, most of the commonly used high-efficiency inhibitors in the polishing liquid have the disadvantages of high toxicity, poor solubility in water and low inhibition efficiency, which are difficult to meet the current needs of industrial production; Third, the passivation film formed by the inhibitors in the polishing liquid has a low hardness and is easily destroyed by silica abrasives, resulting in defects such as corrosion and scratches on the copper surface; Fourth, the polishing liquid currently on the market is difficult to simultaneously meet the requirements of high removal rate and low surface roughness.

[0003] Therefore, developing a copper CMP polishing liquid that is harmless to equipment and operators, can effectively resist corrosion and scratches, and simultaneously meet the requirements of high removal rate and low surface roughness is of great significance for improving the processing efficiency and product quality of the copper wiring layer of integrated circuits. Summary of the invention

[0004] The object of the present invention is to provide a novel alkaline copper CMP polishing liquid and a preparation method thereof to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A novel alkaline copper CMP polishing liquid comprises an abrasive, a pH regulator, a complexing agent, an oxidant, a composite inhibitor, a lubricant and deionized water, wherein the abrasive is SiO 2 The pH regulator is a potassium hydroxide solution, the composite inhibitor includes dodecylbenzenesulfonic acid and 2-aminobenzimidazole, and the lubricant includes multi-walled carbon nanotubes.

[0007] As a further solution of the present invention: the average particle size of the abrasive is 62.5 nm and the concentration is 0.5 wt %.

[0008] As a further solution of the present invention: the pH value of the polishing liquid adjusted by the pH adjuster is in the range of 8-8.5.

[0009] As a further embodiment of the present invention: the complexing agent includes glycine at a concentration of 2 wt %.

[0010] As a further solution of the present invention: the oxidant includes hydrogen peroxide with a concentration of 1 wt %.

[0011] As a further solution of the present invention: the concentration of dodecylbenzenesulfonic acid is 0.2 mM, and the concentration of 2-aminobenzimidazole is 0.8 mM.

[0012] As a further solution of the present invention: the concentration of the multi-walled carbon nanotubes is 0.02 mM.

[0013] Another object of the present invention is to provide a method for preparing a novel alkaline copper CMP polishing liquid, which specifically comprises the following steps:

[0014] Step 1: 0.2 mM dodecylbenzene sulfonic acid and 0.02 mM multi-walled carbon nanotubes were added to deionized water and ultrasonicated for 8 hours to obtain high-quality single tubes;

[0015] Step 2: Dissolve 0.5 wt % silica sol, 2 wt % glycine, 0.2 mM dodecylbenzene sulfonic acid, 0.5 wt % hydrogen peroxide, 0.8 mM 2-aminobenzimidazole and 0.02 mM multi-walled carbon nanotubes in deionized water.

[0016] Step 3: After sufficient stirring and dissolution, adjust the pH to 8.5 using potassium hydroxide.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The inhibitors dodecylbenzenesulfonic acid and 2-aminobenzimidazole used in the polishing liquid of the present invention are easily soluble in water, non-toxic and harmless, green and environmentally friendly, and have high inhibition efficiency, which can effectively reduce the corrosion of the polishing liquid on the copper surface;

[0019] 2. Multi-walled carbon nanotubes are added to the polishing liquid of the present invention as lubricants, which effectively reduce the scratches on the copper surface caused by silica abrasives;

[0020] 3. The polishing liquid of the present invention is an alkaline polishing liquid, which will not corrode equipment or harm operators;

[0021] 4. The polishing liquid of the present invention can ensure a high copper removal rate while obtaining excellent surface quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1This is the scanning electron microscope (SEM) image of a single WMCNTs after ultrasound.

[0023] Figure 2 SEM and atomic force microscopy (AFM) images of the copper surface after CMP.

[0024] Figure 3 EIS diagram and Tafel curve of copper surface.

[0025] Figure 4 The surface roughness of copper after polishing using a polishing solution having a pH of 6, 0.1 wt% silica sol, 1 M glycine, 1 wt% hydrogen peroxide, 30 mM TAZ and 1 mM 5-MBTA in Comparative Example 1.

[0026] Figure 5 The surface roughness of copper after polishing using a polishing solution having a pH of 8.5, 0.5 wt % silica sol, 3 ml / L JFCE, 2 wt % glycine, 40 ppm TAZ and 0.3 wt % hydrogen peroxide in Comparative Example 2.

[0027] Figure 6 The surface roughness of copper after polishing using a polishing solution having a pH of 9, 5 wt % silica sol, 3 ml / L JFCE, 2 wt % glycine, 0.5 wt % sarcosine and 1 wt % hydrogen peroxide in Comparative Example 3.

[0028] in:

[0029] CMP: The full English name is Chemical Mechanical Polishing, and the Chinese meaning is chemical mechanical polishing.

[0030] TAZ: The full English name is 1,2,4-Triazole, and the Chinese meaning is 1,2,4-triazole.

[0031] 5-MBTA: The full English name is 5-Methyl-1H-benzotriazole, and the Chinese meaning is 5-methylbenzotriazole.

[0032] SiO2: The full English name is Silicon dioxide, and the Chinese meaning is silicon dioxide.

[0033] DBSA: The full English name is Dodecylbenzene sulfonic acid, and the Chinese meaning is dodecylbenzenesulfonic acid.

[0034] 2-ABI: The full English name is 2-aminobenzimidazole, and the Chinese meaning is 2-aminobenzimidazole.

[0035] WMCNTs: The full English name is Multi-walled carbon nanotubes, and the Chinese meaning is multi-walled carbon nanotubes.

[0036] EIS: The full English name is Electrochemical impedance spectroscopy, and the Chinese meaning is electrochemical impedance spectroscopy. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] The polishing machine is Alpsitec E460E (made in France), the polishing pad model is IC-1010, and the process parameters are shown in Table 1. The composition and parameters of the polishing liquid: the abrasive is SiO 2 (average particle size of 62.5nm, concentration of 0.5wt%), pH regulator is potassium hydroxide solution (adjust the pH value of the polishing liquid to 8.5), complexing agent is glycine (concentration of 2wt%), oxidant is hydrogen peroxide (concentration of 1wt%), DBSA and 2-ABI are used as composite inhibitors (concentrations of 0.2mM and 0.8mM respectively), lubricant is MWCNTs (0.2mM DBSA is added and ultrasonicated in deionized water for 8 hours (ultrasonic power and frequency are set to: 120W and 55kHz), concentration is 0.02mM), and the single tube structure obtained after ultrasonication is as shown Figure 1 As shown, the remaining components are deionized water. The removal rate test was carried out using a 3-inch copper target produced by Beijing Tebo Technology Co., Ltd., and the calculation method was the weight loss method; the surface roughness test was carried out using a 3-inch silicon substrate copper-plated film produced by SKWAssociates. The polishing pad was trimmed with a diamond dresser for 5 minutes before each polishing. The electrochemical impedance spectroscopy (EIS) and dynamic polarization (Tafel) curves were tested using a CHI660E electrochemical workstation (Shanghai Chenhua) to characterize the strength of the passivation film on the copper surface and the inhibition efficiency of the inhibitor. Before weighing, surface roughness and passivation film strength tests, the target and the film were cleaned with deionized water and dried with nitrogen. After polishing, the removal rate of the copper target can reach 529nm / min, and the surface roughness Sq reaches 0.63nm (detection range is 10×10μm 2 ), the surface flatness is good, and there are no scratches, pits and other defects, which meets the requirements of industrial production, such as Figure 2 shown.

[0040] Figure 3 The EIS and Tafel curves of the passivation film formed by DBSA and 2-ABI on the copper surface are shown in Table 2. The results show that the composite passivation film formed by 0.2mM DBSA+0.8mM 2-ABI has higher resistance, lower corrosion current density and higher inhibition efficiency, indicating that the passivation film can effectively prevent the polishing liquid from corroding the copper surface and is an excellent inhibitor.

[0041] Table 1 CMP process parameters

[0042]

[0043] Table 2 Passivation film strength formed by inhibitor on copper surface

[0044]

[0045]

[0046] Comparative Example 1:

[0047] Comparative Example 1 Polishing liquid composition: abrasive is silicon dioxide (SiO 2 , average particle size is 80nm, concentration is 0.1wt%), the oxidant is hydrogen peroxide (concentration is 1wt%), the pH adjuster is nitric acid and potassium hydroxide (adjust the pH value of the polishing liquid to 6), the complexing agent is glycine (concentration is 0.1M), the inhibitor is TAZ and 5-MBTA (concentrations are 30mM and 1mM respectively), and the remaining ingredients are water.

[0048] Comparative Example 1 used surface roughness and material removal rate as evaluation indicators, and explored the effect of the composite inhibitor of 1,2,4-triazole (TAZ) and 5-methylbenzotriazole (5-MBTA) on copper CMP through the experimental method of polishing and surface morphology test. The polishing equipment was UNIPOL-1200S automatic pressure grinding and polishing machine produced by Shenyang Kejing Automation Equipment Co., Ltd., and the polishing pad was IC1010 / SUBA IV polyurethane. Polishing process parameters: polishing pressure was 3.5psi, the speed of the polishing head and polishing disc was 60rpm, the polishing time was 1min, and the polishing liquid flow rate was 100mL / min.

[0049] A copper sample with a diameter of 50.8 mm and a purity of 99.99% was used as the polished material. A microbalance (MSA225S, Sartorius, with an accuracy of 10 μg) was used to weigh the copper before and after polishing, and the removal rate was calculated using the weight loss method. An optical 3D surface profiler (SuperView W1, Chotest) was used to measure the surface morphology and roughness, with a scanning area of ​​97.9 μm × 97.9 μm. Figure 4 As shown, the copper surface roughness after polishing with 30mM TAZ+1mM 5-MBTA reaches 3nm.

[0050] Comparative Example 2

[0051] Comparative Example 2 Polishing liquid composition: abrasive is silicon dioxide (SiO 2 , average particle size is 10nm, concentration is 0.5wt%), the oxidant is hydrogen peroxide (concentration is 0.3wt%), the pH adjuster is potassium hydroxide (adjust the pH value of the polishing liquid to 8.5), the complexing agent is glycine (concentration is 2wt%), the inhibitor is 1,2,4 triazole (TAZ, concentration is 40ppm) and phytic acid (concentration is 2ml / L), the surfactant is fatty alcohol polyoxyethylene ether (JFCE, concentration is 3ml / L), and the remaining ingredients are water.

[0052] Comparative Example 2 used surface roughness as the evaluation index and explored the effect of phytic acid on copper CMP by polishing and surface morphology test. The polishing equipment was an E460E polishing machine produced in France, and the polishing pad IC 1000. Polishing process parameters: polishing pressure was 1.5 psi, the speed of the polishing head and the polishing disc were both 87 rpm, the polishing time was 3 min, and the polishing liquid flow rate was 300 mL / min.

[0053] A copper sample with a diameter of 3 inches and a purity of 99.99% was used as the polished material. A microbalance (MettlerToledo AB204-N, with an accuracy of 10 μg) was used to weigh the sample before and after polishing, and the removal rate was calculated using the weight loss method. An atomic force microscope (Agilent-5600LS) was used to measure the surface morphology and roughness, with a scanning area of ​​10 μm × 10 μm. Figure 5 As shown, the copper surface roughness after polishing with 2 ml / L of phytic acid reaches 1.68 nm.

[0054] Comparative Example 3

[0055] Comparative Example 3 Polishing liquid composition: abrasive is silicon dioxide (SiO 2, average particle size is 100nm, concentration is 0.5wt%), the oxidant is hydrogen peroxide (concentration is 1wt%), the pH adjuster is nitric acid and potassium hydroxide (adjust the pH value of the polishing liquid to 9), the complexing agent is glycine and sarcosine, the surfactant is fatty alcohol polyoxyethylene ether (JFCE, concentration is 3ml / L), and the remaining ingredients are water.

[0056] Comparative Example 3 used surface roughness as the evaluation index and explored the effect of sarcosine on copper CMP by polishing and surface morphology test. The polishing equipment was a French-made E460E polisher with a polishing pad IC 1000. Polishing process parameters were: polishing pressure of 1.5 psi, polishing head and polishing disc speed of 87 rpm, polishing time of 3 min, and polishing liquid flow rate of 300 mL / min.

[0057] Comparative Example 3: A copper sample with a diameter of 3 inches and a purity of 99.99% was used as the polished material. A microbalance (Mettler Toledo AB204-N, with an accuracy of 10 μg) was used to weigh the sample before and after polishing, and the removal rate was calculated by the weight loss method. An atomic force microscope (Agilent-5600LS) was used to measure the surface morphology and roughness, with a scanning area of ​​10 μm×10 μm. Figure 6 As shown, the copper surface roughness after polishing with 0.5wt% sarcosine + 2wt% glycine reaches 1.01nm.

[0058] Table 3: Performance comparison of different types of polishing fluids

[0059]

[0060]

[0061] It can be seen from Table 3 that compared with the prior art solution, the copper removal rate of the polishing liquid of the present application can reach 529 nm / min, the surface roughness Sq reaches 0.63 nm, and there are no scratches and pits on the surface, indicating that this polishing liquid can effectively regulate the removal rate and improve the surface quality; the polishing liquid of the present application adds MWCNTs as a lubricant, which effectively reduces the scratches on the copper surface by the abrasive; the polishing liquid of the present application is an alkaline polishing liquid, which is friendly to equipment and operators; the inhibitors DBSA and 2-ABI used in the polishing liquid of the present application are non-toxic and harmless, easily soluble in water, and can adhere to a dense passivation film on the copper surface, effectively preventing the polishing liquid from corroding the copper surface.

[0062] It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Although this specification is described in accordance with the implementation modes, not every implementation mode includes only one technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A novel alkaline copper CMP polishing liquid, characterized in that: The invention comprises an abrasive, a pH regulator, a complexing agent, an oxidant, a composite inhibitor, a lubricant and deionized water, wherein the abrasive is SiO2, the pH regulator is a potassium hydroxide solution, the composite inhibitor comprises dodecylbenzenesulfonic acid and 2-aminobenzimidazole, and the lubricant comprises multi-walled carbon nanotubes.

2. A novel alkaline copper CMP polishing liquid according to claim 1, characterized in that: The abrasive has an average particle size of 62.5 nm and a concentration of 0.5 wt %.

3. A novel alkaline copper CMP polishing liquid according to claim 2, characterized in that: The pH adjusting agent adjusts the pH value of the polishing liquid to a range of 8-8.

5.

4. A novel alkaline copper CMP polishing liquid according to claim 1, characterized in that: The complexing agent includes glycine at a concentration of 2 wt%.

5. A novel alkaline copper CMP polishing liquid according to claim 1, characterized in that: The concentration of dodecylbenzenesulfonic acid is 0.2 mM, and the concentration of 2-aminobenzimidazole is 0.8 mM.

6. A method for preparing a novel alkaline copper CMP polishing liquid, according to any one of claims 1 to 5, characterized in that: The specific steps include: Step 1: 0.2 mM dodecylbenzene sulfonic acid and 0.02 mM multi-walled carbon nanotubes were added to deionized water and ultrasonicated for 8 hours to obtain high-quality single tubes; Step 2: dissolving 0.5 wt % silica sol, 2 wt % glycine, 0.2 mM dodecylbenzene sulfonic acid, 0.5 wt % hydrogen peroxide, 0.8 mM 2-aminobenzimidazole and 0.02 mM multi-walled carbon nanotubes in deionized water; Step 3: After sufficient stirring and dissolution, adjust the pH to 8.5 using potassium hydroxide.

Citation Information

Cited By

  • Application of corrosion inhibitor in copper chemical mechanical polishing solution, copper chemical mechanical polishing solution and application of copper chemical mechanical polishing solution

    CN122358202A